Special Features Of The ‘Women Of Ansar’: An Analysis From Ṣaḥiḥ Al Bukhari And Muslim - Nur Saadah Hamisan @Khair (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BI004 41-51